Customs in the making of African Law - (:unkn) unknown (My University, 2021)
In his circular of 8 November 1941, Governor Félix Éboué established a real political program for Africa, which allows us to affirm that Free France, which had become a State, had an African policy as early as 1941. "Africa must keep, while perfecting it, an African law," wrote Éboué in his circular. In other words, customs should be preserved and evolve from within, rather than being crushed. This policy was not adopted at the Brazzaville conference, nor after the independence of sub-Saharan African countries. Today, however, jurists are calling for the role of customs to be reconsidered and for their innovative character to be understood. We will call this approach "legal Afropluralism".
Keywords: African Research